Reviewing the validity of existing measures of emergency physician workload-a scoping review - Foster, Steven; Hegde, Sudeep; Pirrallo, Ronald; Liu, Dixizi; Taaffe, Kevin (International journal for quality in health care, 2025)
Increasing workload and overload for emergency physicians is associated with increased admission rates, staff attrition, burnout, and decreased quality of care. Despite this growing challenge, few interventions exist to mitigate emergency physician overload, with one reason being a lack of tailored and validated measures of emergency physician workload. This scoping review identifies existing emergency physician workload measures and assesses their validity in the context of emergency physician workflows. A scoping review was conducted following the PRISMA-Scr (Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews) guidelines, using five databases to survey literature in the areas of human factors, psychology, and medicine. The search criteria focused on the development, usage, and validity of measures of emergency physician workload in medical settings. Seventy-two articles met the inclusion criteria for this review. Fifty-one included articles utilized objective measures of emergency physician workload, 32 articles utilized subjective measures of emergency physician workload, and 11 articles utilized a combination of both objective and subjective measures. Of the included articles, 18 provided a justification for their usage of specific workload metrics for their study, with citation of previous usage being the most common justification for usage. While several measures of emergency physician workload were identified in this scoping review, we find that there is a lack of contextual validity for these measures. Given the inherent complexity of emergency physician work, the researched consequences of increased emergency physician workload, and the lack of successful workload-reducing interventions in emergency medicine, it is evident that measures tailored to the specific work contexts of emergency physicians are increasingly necessary. This study concludes that there is a clear need for the development of new measures of emergency physician workload that are valid in the context of emergency physicians' workflows.